(3GdGJLGgGJ GdMOjKI aj GdJMdjd GdeGdj (B/s - (3GdMjGdj, hdjO fGLjs ((3YeGf(B: s (3EKQGA ddfTQ(B, s, 2008)
(3ebheGJ hNWhGJ GdJMdjd GdeGdj,GdWQb hGdCSGdjH GdafjI GdeSJNOeI aj GdJMdjd GdeGdj,GdfSH GdeGdjI dbGFeI GdONd,GdfSH GdeGdjI GdeTJQcI hGdfSH GdeYjGQjI,GdebGQfGJ GdQCSjI,GdCSGdjH GdMOjKI aj GdJMdjd GdeGdj,JMdjd eDTQGJ fJGFL GdCOGA,JMdjd GdeHjYGJ,JMdjd bhi GdYed GdMj,GdJMdjd GdeGdj dCZQGV GdJfHD HGdaTd GdeGdjs
(3HHdjhZQGajG(B:(3U U(B.205-208s
Keywords: (3GdeGdjI GdYGeIs